Isotopic Traceability (13C and 18O) of Greek Olive Oil - Petros Karalis; Anastasia Elektra Poutouki; Theodora Nikou; Maria Halabalaki; Charalampos Proestos; Effie Tsakalidou; Sofia Gougoura; George Diamantopoulos; Maria Tassi; Elissavet Dotsika (Molecules, 2020)
In recent years, isotopic analysis has been proven a valuable tool for the determination of the origin of various materials. In this article, we studied the 18O and 13C isotopic values of 210 olive oil samples that were originated from different regions in Greece in order to verify how these values are affected by the climate regime. We observed that the δ18O isotopic values range from 19.2 ‰ to 25.2 ‰ and the δ13C values range from −32.7 ‰ to −28.3 ‰. These differences between the olive oils’ isotopic values depended on the regional temperature, the meteoric water, and the distance from the sea. Furthermore, we studied the 13C isotopic values of biophenolic extracts, and we observed that they have same capability to differentiate the geographic origin. Finally, we compared the isotopic values of Greek olive oils with samples from Italy, and we concluded that there is a great dependence of oxygen isotopes on the climatic characteristics of the different geographical areas.